In the Dominion of the Realms - Estrabou, C.; Sosa, C; Crocco, L. (Journal of Biology Education, 1999)
The problem of the classification of biologic diversity comes from Aristotle, although it has nos beco resolved yet. At present, the most extensively used system is Whittaker's "Five Kingdoms", based upon morphological patterns, but recentty the idea of Dominion. based on molecular patterns, has been proposed. Modern lab tecirniques and the discovery of new organisms (like Archeobacteria) lcd to modify the classffication's entenon. The purpose of this study is So take a glance of the different classification systems. The value of each one is discussed according So its plrpose.